Dermoscopy in Monitoring and Predicting Therapeutic Response in General Dermatology (Non-Tumoral Dermatoses): An Up-To-Date Overview - Enzo Errichetti (Adis, Springer Healthcare, 2020)
Abstract Besides the well-known use in supporting the non-invasive diagnosis of non-tumoral dermatoses (general dermatology), dermoscopy has been shown to be a promising tool also in predicting and monitoring therapeutic outcomes of such conditions, with the consequent improvement/optimization of their treatment. In the present paper, we sought to provide an up-to-date overview on the use of dermoscopy in highlighting response predictor factors and evaluating therapeutic results in the field of general dermatology according to the current literature data. Several dermatoses may somehow benefit from such applications, including inflammatory conditions (psoriasis, lichen planus, dermatitis, granulomatous conditions, erythro-telangiectatic rosacea, Zoon balanitis and vulvitis, cutaneous mastocytosis, morphea and extra-genital lichen sclerosus), pigmentary disorders (vitiligo and melasma) and infectious dermatoses (scabies, pediculosis, demodicosis and viral warts).